Cytogenetic studies in two geographical stocks of Heteropneustes fossilis (Bloch) - KUSHWAHA, B; NAGPURE, N S; SRIVASTAVA, SATISH K; PONNIAH, A G (The Indian Journal of Animal Sciences, 2014)
Studies have been undertaken in two morphologically different stocks of Heteropnuestesfossilis from distinct geographic locations, to detect differences at chromosomal level using conventional karyotyping and NOR banding. The diploid chromosome was 2n=56 with chromosomal formula = 14m+20sm+1 2st+10t (FN=90). Prominent NOPs were located on short arm of 1 pair of submetacentric chromosome number 12 in both the stocks and no variation in karyomorphology and NOR band pattern has been found between 2 stocks.